Analisis Resepsi Komunikasi Konteks Rendah pada Iklan Introducing iPhone 15 - Hamsinah Hamsinah; Fransiska Angelina Widiyanti; Widyarini Ridwan (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Advertisements have a communicative meaning through the messages conveyed to consumers. The use of language is also important in accordance with the symbols and implied meanings. This study aims to analyse low-context communication reception in the iPhone 15 (2023) advertisement. The iPhone 15 (2023) advertisement was chosen because it is considered to have low-context communication characteristics, namely emphasising the explicit and direct delivery of information, using language that is easy to understand, and minimising the use of symbolism and implied meanings. This study uses a qualitative method with reception analysis techniques. The results show that the reception of low-context communication in the iPhone 15 (2023) advertisement is generally positive. Informants understand the information conveyed in the advertisement well and show a positive attitude towards the use of low-context communication culture in the Introducing iPhone 15 advertisement. However, there are also informants who show a negotiating position towards the use of this communication culture. This study is expected to contribute to the understanding of low-context communication reception in an advertisement, particularly in the iPhone 15 (2023) advertisement.